Serum neurofilament light chain in patients with acute cerebrovascular events. (24th January 2018) - De Marchis, G. M.; Katan, M.; Barro, C.; Fladt, J.; Traenka, C.; Seiffge, D. J.; Hert, L.; Gensicke, H.; Disanto, G.; Sutter, R.; Peters, N.; Sarikaya, H.; et al.
Abstract : Background and purpose: Serum neurofilaments are markers of axonal injury. We addressed their diagnostic and prognostic role in acute ischemic stroke (AIS) and transient ischemic attack (TIA). Methods: Nested within a prospective cohort study, we compared levels of serum neurofilament light chain (sNfL) drawn within 24 h from symptom onset in patients with AIS or TIA. Patients without magnetic resonance imaging on admission were excluded. We assessed whether sNfL was associated with: (i) clinical severity on admission, (ii) diagnosis of AIS vs. TIA, (iii) infarct size on admission magnetic resonance diffusion‐weighted imaging (MR‐DWI) and (iv) functional outcome at 3 months. Results: We analyzed 504 patients with AIS and 111 patients with TIA. On admission, higher National Institutes of Health Stroke Scale (NIHSS) scores were associated with higher sNfL: NIHSS score < 7, 13.1 pg/mL [interquartile range (IQR), 5.3–27.8]; NIHSS score 7–15, 16.7 pg/mL (IQR, 7.4–34.9); and NIHSS score > 15, 21.0 pg/mL (IQR, 9.3–40.4) ( P = 0.01). Compared with AIS, patients with TIA had lower sNfL levels [9.0 pg/mL (95% confidence interval, 4.0–19.0) vs. 16.0 pg/mL (95% confidence interval, 7.3–34.4), P < 0.001], also after adjusting for age and NIHSS score ( P = 0.006). Among patients with AIS, infarct size on admission MR‐DWI was not associated with sNfL, either in univariate analysis ( P = 0.15) or after adjusting for age and NIHSS score on admission ( P = 0.56). Functional outcome 3 months after stroke was not associated with sNfL after adjusting for established predictors. Conclusions: In conclusion, among patients admitted within 24 h of AIS or TIA onset, admission sNfL levels were associated with clinical severity on admission and TIA diagnosis, but not with infarct size on MR‐DWI acquired on admission or functional outcome at 3 months.